One step selective partition of ε-polylysine present in broth cultures in ionic liquid-based aqueous biphasic systems. Issue 3 (11th February 2021) - Sequeira, Rosy Alphons; Sharma, Mukesh; Pereira, Matheus M.; Singh, Nripat; Bhattacharya, Sourish; Chudasama, Nishith A; Prasad, Kamalesh
ABSTRACT: Four different ionic liquids were synthesized, characterized and used with polypropylene glycol for the formation of aqueous biphasic systems and were used to selectively separate ε-PL from culture broth. It was observed that the partition of ε-PL to the IL-rich phase was achieved, and with pure ε-PL, the extraction efficiency was found to be 99.92% while with culture broth, it was 93.42% for the ABS formed with 2-hydroxyethylammonium formate. Preservation of the chemical and structural stability of ε-PL in the ABSs indicated the potential of such systems as remarkable platform for the selective separation of ε-PL from the culture broth.